Implementation of Forward Chaining in a Web-Based Expert System for Passport Services - Dwi Handoko Putra; Nurabiyyu Rahditiantoro (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
In the digital era, technology has become a crucial component in public services. The Class I Immigration Office TPI Yogyakarta is experiencing an increase in passport applicants, necessitating more efficient service delivery. An Expert System, which simulates the knowledge of a human expert, can enhance the efficiency of passport services by gathering and organizing knowledge within a database. Expert Systems, which have been widely applied in the healthcare sector, also hold significant potential in passport services. Many passport applicants lack a clear understanding of the required information, leading to confusion and delays. An Expert System helps applicants access accurate information regarding passport types and provides recommendations for the most suitable option. It also improves service quality by reducing errors and saving time. The selection of an Expert System is based on its ability to effectively store and manage expert knowledge, while offering accurate and fast solutions and recommendations. This system benefits passport applicants, immigration officers, and the government by improving the efficiency and effectiveness of public services and increasing public satisfaction. Additionally, the Expert System is designed to be flexible and adaptable to changes in regulations or procedures.